2016
DOI: 10.1111/cmi.12682
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of epithelial cell lysosomal integrity induced by bacterial cholesterol-dependent cytolysins

Abstract: Bacterial pathogens can interfere during infection with host cell organelles, such as mitochondria, the endoplasmic reticulum‐Golgi system or nuclei. As important cellular functions are often compartmentalized in these organelles, their targeting allows pathogens to manipulate key host functions during infection. Here, we identify lysosomes as a new class of organelles targeted by the pathogenic bacterium Listeria monocytogenes. We demonstrate that extracellular Listeria, via secretion of the pore‐forming toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 60 publications
(98 reference statements)
0
25
0
Order By: Relevance
“…The strains used in this study were Listeria monocytogenes strain EGD (BUG 600), an L. monocytogenes EGD Δ hly mutant (BUG 3650 [58]), L. monocytogenes EGDe.PrfA* (BUG 3057), and Salmonella Typhimurium strain SR-11 (BUG 3044; kind gift of F. Norel and V. Robbe-Saule, Institut Pasteur, Paris, France). Listeria strains were grown in brain heart infusion (BHI) broth or agar plates (BD Difco), whereas Salmonella Typhimurium was grown in Luria-Bertani (LB) broth or agar plates (BD Difco).…”
Section: Methodsmentioning
confidence: 99%
“…The strains used in this study were Listeria monocytogenes strain EGD (BUG 600), an L. monocytogenes EGD Δ hly mutant (BUG 3650 [58]), L. monocytogenes EGDe.PrfA* (BUG 3057), and Salmonella Typhimurium strain SR-11 (BUG 3044; kind gift of F. Norel and V. Robbe-Saule, Institut Pasteur, Paris, France). Listeria strains were grown in brain heart infusion (BHI) broth or agar plates (BD Difco), whereas Salmonella Typhimurium was grown in Luria-Bertani (LB) broth or agar plates (BD Difco).…”
Section: Methodsmentioning
confidence: 99%
“…LCD is characterized by lysosomal membrane permeabilization (LMP) and mediated by the release of lysosomal cathepsins into the cytoplasm, which causes caspase-dependent and caspase-independent cell death (Windelborn and Lipton, 2008;Jiang et al, 2016;Clerc et al, 2018). To date, many pathogenic factors that induce LMP have been discovered, including ROS, lysosomotropic drugs, bacterial and viral products (de Duve, 2005;Huang et al, 2017;Malet et al, 2017). Studies regarding LMP in neuronal ischemic injury have revealed that ROS generation, calcium overload and calpain activation account for the induction of LMP and consequent neuronal death (Yamashima and Oikawa, 2009;Lipton, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that the secreted pore-forming toxin LLO induces LMP and the release of cathepsins in the host cytosol via its pore-forming activity [90]. Other cholesterol-dependent cytolysins, such as perfringolysin O and pneumolysin, secreted by other extracellular pathogenic bacteria, also induce LMP [90]. These findings unveil a novel activity of bacterial cholesterol-dependent cytolysins that may interfere with important host cellular pathways linked to lysosomal functions.…”
Section: Interaction With Lysosomesmentioning
confidence: 98%
“…Different stress conditions may alter the integrity of lysosomal membranes (a process known as lysosomal membrane permeabilisation (LMP)), resulting in the leakage of lysosomal content to the cytosol. It was recently shown that the secreted pore-forming toxin LLO induces LMP and the release of cathepsins in the host cytosol via its pore-forming activity [90]. Other cholesterol-dependent cytolysins, such as perfringolysin O and pneumolysin, secreted by other extracellular pathogenic bacteria, also induce LMP [90].…”
Section: Interaction With Lysosomesmentioning
confidence: 99%